1999
DOI: 10.1002/jlb.66.5.765
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages: important accessory cells for reproductive function

Abstract: Macrophages are found throughout reproductive tissues. To determine their role(s), we have studied mice homozygous for a null mutation (Csfm(op)) in the gene encoding the major macrophage growth factor, colony-stimulating factor-1 (CSF-1). Both male and female Csfm(op)/Csfm(op) mice have fertility defects. Males have low sperm number and libido as a consequence of dramatically reduced circulating testosterone. Females have extended estrous cycles and poor ovulation rates. CSF-1 is the principal growth factor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 69 publications
2
120
0
5
Order By: Relevance
“…The important role of CSF-1 in ovulation, preimplantation, placental function, regulation of the estrous cycle, and lactation has been described previously (for reviews, see Pollard and Stanley 5 and Cohen et al 6 ). Both the CSF-1-deficient Csf1 op /Csf1 op mice and the CSF-1R-null mice have increased estrous cycle times, a failure of mammary gland development during pregnancy, and a decreased male libido.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The important role of CSF-1 in ovulation, preimplantation, placental function, regulation of the estrous cycle, and lactation has been described previously (for reviews, see Pollard and Stanley 5 and Cohen et al 6 ). Both the CSF-1-deficient Csf1 op /Csf1 op mice and the CSF-1R-null mice have increased estrous cycle times, a failure of mammary gland development during pregnancy, and a decreased male libido.…”
Section: Resultsmentioning
confidence: 66%
“…5,6,51 Despite their powdered chow and milk formula diet, these mice still exhibit a decreased adult body weight and a markedly retarded growth rate ( Figure 2A). We previously showed that the full-length transgene, TgC, is able to fully restore the growth retardation in Csf1 op /Csf1 op ; TgC/ϩ mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Csf1 op/op mice are severely depleted in ovarian, uterine and placental macrophages. 128 Macrophages are important accessory cells in reproduction and it is the absence of CSF-1-mediated tissue macrophage regulation that is responsible for the primary fertility defects observed in Csf1 op/op mice.…”
Section: Resident Macrophages and Regenerationmentioning
confidence: 99%
“…Also unaffected in op/op mice are dendritic cells and Langerhans cells. In addition to macrophage and osteoclast deficiencies, the animals have developmental defects of the nervous and reproductive systems, which may reflect roles of embryonic macrophages [29, [139][140][141][142]. The interpretation of the op/op phenotype is difficult because of transplacental trafficking of CSF-1, but recent evidence indicates that some embryonic macrophage populations can develop normally even when the mother is also op/op [143].…”
Section: Growth Factorsmentioning
confidence: 99%